Depressive Disorder in The Elderly with Comorbidity in Prima Medika Clinic, Semarang - Eviana Budiartanti Sutanto; Perigrinus Hermin Sebong (Soegijapranata Catholic University, 2023)
Background: Diabetes Mellitus and hypertension patients have higher risks of experiencing mental disorders such as depression and or anxiety. Objective: assess the frequency and severity of depression as well as identify the risk factors of patients with chronic disease and also other factors influencing depression in PROLANIS patients in Prima Medika Primary Clinic, Semarang Indonesia. Method: A cross-sectional study, targeting PROLANIS patients registered at Prima Medika Primary Clinic in Semarang, Indonesia. Participants were selected through purposive sampling, during a period from February to May 2021. Participants targeted were DM, Hypertension, or a combination of hypertension and diabetic type 2 patients. The Indonesia Ministry of Health Clinical Criteria was used for the Metabolic Syndrome assessment. Result: Among 68 respondents, 15 (22.05%) respondents suffered from mild depression and 6 (8.82%) respondents suffered from major depression. Mostly, their education level is High School (55.9%), are married (73.5%), have fixed income (55.8%), and are non-smokers. The number of participants suffering from hypertension is larger than those who suffer from DM and DM + Hypertension. Correlation test results find a relationship between disease diagnosis and the case of depression in PROLANIS participants (p-value 0.05). Conclusion : Depression, DM, and hypertension are diseases in which the number of cases keeps increasing. Early detection of depression needs to be improved to promote the successful management of diabetes and hypertension.